Community Service Collaboration of Higher Education Institutions: Integrating Technology in Promoting Baduy Luar Ecotourism as an Effort for Local Potential-Based Development - Umban Adi Jaya; Hasti Pramesti; Amna Mawardi; Galih Raspati; Farhan Hamdallah (Transpublika Publisher, 2025)
The Baduy Luar community in Lebak Regency, Banten, possesses unique cultural assets and significant potential in handicrafts, agriculture, and culture-based ecotourism. This Community Service Program (PKM) was conducted in Baduy Luar, Lebak Regency, Banten, with the aim of enhancing digital literacy and entrepreneurial capacity among the local community to support the promotion of cultural-based ecotourism. The Baduy Luar community possesses great potential in handicrafts, agriculture, and tourism, yet still faces limitations in digital promotion and tourism management. This program applied a participatory and contextual approach involving 70 participants, including youth, MSME actors, and ecotourism practitioners. The experiential learning method enabled participants to learn through direct practice, covering smartphone use, tourism documentation, and promotion via social media platforms such as Instagram, TikTok, YouTube, WhatsApp Business, and Facebook. The results showed significant improvement in the community’s skills in utilizing digital technology for ecotourism promotion and cultural documentation. Furthermore, a positive synergy was established between universities and the local community, where academics acted as facilitators of digital knowledge while the community members served as the main actors in implementing digital-based promotion. This program contributed not only to enhancing technical skills but also to preserving cultural identity through digital documentation. In the long term, the program is expected to increase community income, sustain community-based tourism promotion, and strengthen local economic independence aligned with the cultural values of the Baduy Luar.